Imunogenesitas Protein Pilli Salmonella Typhi Pada Mencit Balb/C Dengan Mengukur Kadar TNF-α: Imunogenesity Of Protein Pilli Salmonella typhi in BALB/c Mice by Measuring TNF-α Controls - Hidayani, Al; Darmawati, Sri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Typhoid fever, often called typhoid disease, is caused by Salmonella enterica subspecies enterica serevoar typhi (Salmonella typhi). The virulence of S.typhi bacteria depends on its ability to invade host cells consisting of several components such as cell wall antigens, flagellum antigens, Vi antigens and pilli antigens. Pilli is one of the virulence factors of S.typhi bacteria, which functions as a tool for adhesion or interaction between bacteria. The study was conducted to determine how the immunogenicity of pilli protein of S.typhi bacteria isolate BA07.4 was immunized in Balb/C mice at varying doses (2-6μg) by measuring TNF- α. The analysis carried out obtained the optimum results of TNF-α levels at a dose of 3μg with an average level of 62.152 pg / ml. In the research conducted, it was found that S.typhi pilli protein can induce specific antibodies against pilli antigens. This shows that the pilli protein is immunogenic, can cause an immune response and can induce antibodies that can recognize the immunized pilli protein sub-unit.